2016
DOI: 10.1177/0265407516650760
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent romantic competence and parenting attitudes

Abstract: The current study examined the distinctive gender-related expressions of adolescent romantic competence and patterns of maternal and paternal attitudes toward daughters' and sons' romantic involvements. Employing a qualitative approach, an in-depth interview assessing romantic competence was given to 69 Israeli adolescents (37 boys) ranging in age from 15 to 18 years, M ¼ 16.74 (SD ¼ .81). In addition, parents were interviewed regarding their attitudes toward their adolescents' romantic involvements. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Regarding this last point, it is essential that future studies examine in more detail how sexuality-specific parenting of fathers and mothers affects boys and girls differently. Indeed, gender intensification theory (Hill and Lynch 1983 ) and emprical research suggests that supportive attitudes towards romantic and sexual experimentation may be sex-linked, and more pronounced in father–son and mother–daughter dyads (Shulman et al 2017 ). Second, our present study was not informative specifically about the development of LGBT adolescents, but rather dealth with adolescents with mostly heterosexual identities.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this last point, it is essential that future studies examine in more detail how sexuality-specific parenting of fathers and mothers affects boys and girls differently. Indeed, gender intensification theory (Hill and Lynch 1983 ) and emprical research suggests that supportive attitudes towards romantic and sexual experimentation may be sex-linked, and more pronounced in father–son and mother–daughter dyads (Shulman et al 2017 ). Second, our present study was not informative specifically about the development of LGBT adolescents, but rather dealth with adolescents with mostly heterosexual identities.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal, not paternal, support was found to predict the pathway of the romantic involvements of their emerging adult children. Past research suggests that while mothers encourage involvement in intimate relationships, fathers tend rather to accept, and even support, romantic and sexual experimentation (Shulman et al, 2016). This could explain why paternal support was not associated with the whereabouts of the romantic explorations of their emerging adult children.…”
Section: Discussionmentioning
confidence: 99%
“…Parenting attitudes and practices regarding adolescent romantic relationships are impacted by gender. For instance, mothers tend to encourage sons and daughters to develop intimacy in relationships, while fathers may encourage sons to experiment in their relationships (Shulman et al., 2017). Further, a meta‐analysis by Widman, Choukas‐Bradley, Noar, Nesi, and Garrett (2016) revealed that parent communication about sex, particularly from mothers, can promote safer sexual behaviors in adolescents.…”
Section: New Directions Over the Last Decadementioning
confidence: 99%